2021
DOI: 10.1016/j.tranon.2021.101090
|View full text |Cite
|
Sign up to set email alerts
|

Non-coding RNAs in pancreatic ductal adenocarcinoma: New approaches for better diagnosis and therapy

Abstract: Highlights Pancreatic ductal adenocarcinoma (PDAC) is one of the most lethal malignancies, which is usually diagnosed at an advanced stage. Non-coding RNAs (ncRNAs) have been recognized to play a central role in PDAC pathogenesis and could be used as biomarkers for PDAC. microRNAs (miRs) can act either as oncogenes or tumour suppressors in PDAC. Long non-coding RNAs (lncRNAs) are around 25% of the total RNA distribution in the human cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 291 publications
(183 reference statements)
0
17
0
Order By: Relevance
“…Due to the development of high-throughput sequencing technology and bioinformatics, circRNAs have attracted increasing attention in the noncoding RNA field and have been discovered and reported as critical regulators of various biological processes, including multiple cancers [ 27 , 28 ]. Currently, the roles of circRNAs in the progression of pancreatic cancer have been revealed in many studies [ 29 ]. Recently, our team reported that circBFAR promotes the progression of PDAC via the miR-34b-5p/MET/Akt axis and that circNFIB1 inhibits lymphangiogenesis and lymphatic metastasis via the miR-486-5p/PIK3R1/VEGF-C axis in pancreatic cancer [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the development of high-throughput sequencing technology and bioinformatics, circRNAs have attracted increasing attention in the noncoding RNA field and have been discovered and reported as critical regulators of various biological processes, including multiple cancers [ 27 , 28 ]. Currently, the roles of circRNAs in the progression of pancreatic cancer have been revealed in many studies [ 29 ]. Recently, our team reported that circBFAR promotes the progression of PDAC via the miR-34b-5p/MET/Akt axis and that circNFIB1 inhibits lymphangiogenesis and lymphatic metastasis via the miR-486-5p/PIK3R1/VEGF-C axis in pancreatic cancer [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-19a-3p was shown to be overexpressed in PDAC with a potential to be used as an early non-invasive diagnostic biomarker but also as a prognostic biomarker. Another study reported the role of miR-29a, miR29b, miR-103, and miR-320 as early diagnostic predictors of PDAC when upregulated [50].…”
Section: Diagnostic Biomarkersmentioning
confidence: 99%
“…For diagnosis of pancreatic cancer, no such FDA approved lncRNA-based diagnosis has been reported so far. However, researches on the development of ncRNA testing as diagnosis or supplementary diagnostic tools for pancreatic cancer have received much attention and revealed some novel markers for pancreatic cancer [149][150][151][152].…”
Section: The Role Of Non-coding Rnas In the Diagnosis Of Pancreatic Cancermentioning
confidence: 99%